AKURASI WAKTU JAM MASJID DI KOTA LHOKSEUMAWE - Ismail, Ismail (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Accuracy of time is very closely related to Islamic law, a lot of worship related to time, such as prayer times, breaking fast and ruling. Without a standard time accuracy, worship can not be done perfectly. The clock is a marker of time that makes it easy for Muslims to carry out worship and social activities. Until now there has been no clock that can survive accuracy with a long time, meaning that all clocks must be calibrated within a certain time span. The time standard for clock calibration is the Atomic Clock time that is on the GPS or on the link http://ntp.bmkg.go.id/Jam.BMKG controlled by Badan Meteorologi Klimatologi dan Geofisika (BMKG). This study tries to find the accuracy of mosque hours and the type of clock used in mosques in Lhokseumawe City by using the method of observation and documentation of 20 mosques selected as samples in the study. The results of observation and documentation show that all mosques (100%) in Kota Lhokseumawe have used the clock as a timemarker, 12 mosques, or 60% of the mosque has been using a digital clock with accuracy of 50% in accordance with the standard and 35% analog clock in accordance with a clock standard observer BMKG.Keywords: Time System, Global Positioning System (GPS), Mosque and Lhokseumawe.